Quasi-Continuous GPS Steep Slope Monitoring: A Multi-Antenna Array Approach - Forward, Troy Andrew (Curtin University, 2002)
This thesis investigates the design, implementation and validation of a multi-antenna GPS system to monitor the displacement of deforming slopes. The system utilises a switched antenna array design allowing data from multiple antennas to be sampled sequentially by one GPS receiver. The system provides quasi-continuous GPS observations that can produce a precise and reliable coordinate time-series of the movement of the slope under consideration. GPS observations and particularly those concerned with the monitoring of steep slopes, are subject to systematic errors that can significantly degrade the quality of the processed position solutions. As such, this research characterises the data in terms of multipath effects, the spectrum of the coordinate time-series, and the carrier to noise power density ratio of the raw GPS observations. Various GPS processing parameters are then investigated to determine optimal processing parameters to improve the precision of the resulting coordinate time-series. Results from data stacking techniques that rely on the daily correlation of the repeating multipath signature find that the GPS data actually decorrelates somewhat from day to day. This can reduce the effectiveness of stacking techniques for the high precision monitoring of steep slopes. Finally, advanced stochastic models such as elevation angle and carrier-to-noise weighting are investigated to optimise the precision of the coordinate time-series data. A new in-line stochastic model is developed based on weighting GPS observations with respect to the level of systematic error present within the data. By using these advanced types of stochastic models, reductions to the noise level of the coordinate time-series of approximately 20 and 25 percent are possible in the horizontal and height components respectively.Results from an extensive field trial of this system on a deforming high-wall of an open-pit mine indicate that approximately 135mm of displacement occurred over the 16-week field trial. The precision of the coordinate time-series for surface stations approaches ±4.Omm and ±5.4mm in the horizontal and height components respectively. For sub-surface stations next to the mine wall, coordinate precision has been determined as ±4.9mm.component and ±7.6mm in the height component respectively.